Viability of bovine demi embryo after splitting of fresh and frozen thawed embryo derived from in vitro embryo production - M Imron; A Boediono; I Supriatna (Jurnal Ilmu Ternak dan Veteriner, 2007)
In vivo embryo production was limited by number of donor, wide variability respond due to superovulation program and also immunoactifity of superovulation hormone (FSH). Splitting technology could be an alternative to increase the number of transferrable embryos into recipien cows. Splitting is done with cutting embryo becoming two equal pieces (called demi embrio) base on ICM orientation.  The objective of this research was to determine the viability of demi embryo obtained from embryo splitting of fresh and frozen thawed embryo. The results showed that demi embryos which performed blastocoel reexpansion 3 hours after embryo splitting using fresh and frozen thawed embryos were 76.9 and 76.2% respectively. Base on existention of inner cell mass (ICM), the number of demi embryos developed with ICM from fresh and frozen thawed embryos were not significantly different (90.6 and 85.7% respectively. The cell number of demi embryo from fresh embryos splitting was not different compared with those from frozen thawed embryos (36.1 and 35.9 respectively). These finding indicated that embryo splitting can be applied to frozen thawed embryos with certain condition as well as fresh embryos. Key Words: In Vitro Embryo, Splitting, Demi Embryo, Cell Number